Religiusity And Bank Products And Their Relationship With Decision Making In Micro Small Medium Business Funding In Pt Bank Muamalat Indonesia - Dwi Hernanik, Nova; Pratikto, Heri (International Journal of Science, Technology & Management, 2022)
This study aims to determine the impact of religion and banking products on the financing decisions of small and medium-sized enterprises (MSMEs) at Bank Muamalat Indonesia Malang Branch. A sample of this survey is an MSME lending customer at Bank Muamalat Indonesia Malang Branch. This study uses primary data through the distribution of quizions. The survey method uses the method of multiple linear regression analysis with SPSS version 18. The results of simultaneous tests based on the findings show that religion and banking products have a common and significant influence on the coefficients of funding. The results show that religion does not have a partial and significant impact on funding decisions. Second, banking products have a partial and significant impact on funding decisions. This study is expected to benefit Bank Muamalat Indonesia, especially PT Bank Muamalat Indonesia Malang Branch, in terms of product design that is more diverse and adapted to the needs of MSME.